EKSISTENSI PEREMPUAN DALAM OPERA BATAK: STUDI KASUS ZULKAIDAH HARAHAP - Jayanti Mandasari Sagala (Universitas Gadjah Mada, 2017)
The art, that is identical with the domination of masculinity or masculine art that happens the Batak Opera musically, cannot be separated with the concept constructed by the patriarchal ideology in the communal. This fact had been challenged by the existence of a woman. Formerly Batak Opera was more masculine art musically, after the existence of Zulkaidah Harahap, Batak Opera now has different path. This study purposes to examine attentively the existence and the importance of Zulkaidah Harahap as a woman in the performing art of Batak Opera in the Batak Toba. This study had been done in two months in Tiga Dolok and Pematang Siantar, North Sumatera, the place where Batak Opera and Zulkaidah Harahap came from. This study uses feminist perspective. It is used to see the women’s problems in the performing art of Batak Opera through the case study and individual life history of a prominent firgure from woman’s tradition of Zulkaidah Harahap with using historical reconstruction method and interview. In this case, the existence of women is seen as a ‘creativity’ in traditional art perspective which is put forward by the theory of George Herzog in his writings “The creativity of tradition music artist”. The other perspective used ini this article is existentialist feminist perspective by Simone de Beauvoir’s theory “The process of women transcendence”. The existence of Zulkaidah Harahap is very important in Batak Opera which is defined as a ‘creativity’ in the performing art of Batak Toba. The creativity of Zulkaidah Harahap in the performing art of Batak Opera can be seen in two things: first, as the one and only woman leader ever to lead a Batak Opera group, second, as the first woman of parmusik (musician) who can play musical instruments to become parmusik which is parallel to men. Through her deeds, she had proved that women, as well as men, are exist for themselves and the self who have the right to be seen as a cultural subject. Through Zulkaidah Harahap, now it is not taboo for Batak women to be parmusik and can be seen in art as subject.